Resting Heart Rate in Children with Crimean-Congo Hemorrhagic Fever: A Tool to Identify Patients at Risk? - İÇAĞASIOĞLU, DİLARA FÜSUN; OFLAZ, MEHMET BURHAN; BOLAT, FATİH; KAYA, ALİ; GÜVEN, AHMET SAMİ; KÜÇÜKDURMAZ, ZEKERİYA; KARAPINAR, HEKİM; GÜLSEVER, OSMAN; Dogan, Melih; Cevit, Omer; İÇAĞASIOĞLU, FÜSUN DİLARA (My University, 2014)
Objective: We aimed to assess the association between resting heart rate (RHR) and severe infection in children with Crimean-Congo hemorrhagic fever (CCHF). Methods: In all, 121 patients under 18 years of age with a laboratory-confirmed diagnosis of CCHF were enrolled in the study. Patients were classified into two groups based on disease severity (severe group and nonsevere group). RHR was measured by electrocardiography (ECG) on admission. Maximum P-wave duration (Pmax), P-wave dispersion (Pd), QRS duration, corrected QT interval, and QT dispersion were also measured. Results: Mean age was 11.43.9 years and 84 patients were male. Twenty-six patients were classified as severe. Patients in this group had a higher RHR (103.6 +/- 10.4vs. 80.5 +/- 8.1, p=0.001) than those with nonsevere disease. There was no difference in Pmax, Pd, QRS duration, QTcmax, or QTc dispersion. The optimal cutoff value of RHR to predict disease severity was>96 beats per minute (bpm), with 70.6% sensitivity and 50.1% specificity. Bleeding, thrombocytopenia (80x10(9)/L), elevated aspartate transaminase (AST) (>208IU/L), elevated alanine transaminase (ALT) (>87IU/L), elevated lactate dehydrogenase (LDH) (>566IU/L), long activated partial thromboplastin time (aPTT) (>42s), and increased hospitalization days were more frequent in patients with RHR >96bpm. Multivariate logistic regression analysis revealed low platelet count (42s), high LDH (>566IU/L), and elevated RHR (>96bpm) as independent risk factors for severe disease. Conclusions: We conclude that elevated RHR was significantly associated with severe disease in children with CCHF, thus offering the potential to identify patients with increased risk.